Exam AZ-500 Microsoft Azure Security Technologies - Warner, Tim (Microsoft Press, 2022)
9+ Hours of Video Instruction Includes coverage of the September 2021 exam updates! Prepare for Microsoft Exam AZ-500, and demonstrate your knowledge of Azure security controls that protect identity, access, data, applications, and networks in cloud and hybrid environments as part of an end-to-end infrastructure. Description Microsoft MVP and Microsoft Certified Azure Solutions Architect Tim Warner walks you through what to expect on the AZ-500 Microsoft Azure Security Technologies exam . The new Azure certifications are aligned to industry job roles; earning Azure certification both validates your specific Azure skill set and increases your value in today's crowded IT job market. Think of the news you've read lately regarding data breaches and ransomware attacks. Knowing how to secure applications and data in the cloud is a business necessity these days, as well as a lucrative job skill. Azure Security Engineer is a popular Microsoft certification for both IT newcomers and veterans. Exam AZ-500 has a reputation as a challenging exam because of the breadth and depth of its content. This training course covers every Exam AZ-500 objective and provides just what you need to pass in a friendly, approachable, and logical way. About the Instructor Tim Warner has been a Microsoft MVP in Cloud/Datacenter Management for five years, and a Microsoft Certified Trainer for more than 20 years. His Microsoft Azure-related O'Reilly Live Training classes reach hundreds of thousands of students around the world. He's written for Microsoft Press, presented at Microsoft Ignite, and contributed to Microsoft open-source projects. He's earned the Azure Security Engineer credential and trains regularly on the topic. You can find Tim on Twitter (@TechTrainerTim) or his website, TechTrainerTim.com . Skill Level Intermediate to Advanced What You Will Learn Complete your AZ-500 exam preparation with confidence Manage identity and access to Azure enforcing least-privilege security Implement Azure platform protection Manage security operations in your Azure environment Secure data and applications Who Should Take This Course Certification candidates preparing for exam AZ-500 Microsoft Azure Security Technologies Any Microsoft certification candidate interested in learning the Azure Security Engineer skill set Any IT professional looking to understand how Microsoft Azure institutes information security Course Requirements Prerequisites: Candidates for ...